Real-world Outcomes Among Patients Treated With Gemcitabine-based Therapy Post-FOLFIRINOX Failure in Advanced Pancreatic Cancer. (December 2019) - Tsang, Erica S.; Spratlin, Jennifer; Cheung, Winson Y.; Kim, Christina A.; Kong, Shiying; Xu, Yuan; Gill, Sharlene
Abstract : Objectives: Limited evidence exists for chemotherapy selection in advanced pancreatic cancer (APC) after first-line FOLFIRINOX. Second-line gemcitabine/nab-paclitaxel (GEMNAB) is publicly funded in the Canadian provinces of Alberta (AB) and Manitoba (MB), but not in British Columbia (BC). We compared population-based outcomes by region to examine the utility of second-line GEMNAB versus gemcitabine (GEM) alone. Methods: We identified patients treated with first-line FOLFIRINOX between 2013 and 2015 across BC, AB, and MB. Baseline characteristics and treatment regimens were compared between AB/MB and BC. Survival outcomes were assessed by the Kaplan-Meier method and compared with log-rank test. Results: A total of 368 patients were treated with first-line FOLFIRINOX (143 AB/MB, 225 BC): median age 61 (interquartile range: 55 to 68) years, 42% comprising female individuals, and 67% with metastatic disease. Receipt of second-line therapy was 48% in AB/MB versus 44% in BC ( P =0.35), and time from diagnosis to second-line therapy was 7.7 (AB/MB) versus 9.4 months (BC; P =0.1). Distribution of second-line GEM use: 73% GEMNAB, 23% GEM (AB/MB) versus 27% GEMNAB, 66% GEM (BC; P <0.001). Median overall survival (OS) from diagnosis was similar: 12.4 (AB/MB) versus 11.5 months (BC; P =0.91). On Cox regression analysis, region was not significant. Secondary survival analysis by second-line regimen demonstrated a median OS of 18.0 months with GEMNAB versus 14.3 months with GEM ( P <0.01). Conclusions: In this population-based comparison of APC patients treated with first-line FOLFIRINOX, survival outcomes were comparable regardless of funded access to second-line GEMNAB. OS by regimen favored second-line GEMNAB, but patient selection may be largely responsible for this difference. Abstract : Supplemental Digital Content is available in the text.